Effect of Lithiation on the Microstructure of a Cobalt Foam Processed by Freeze Casting. Issue 10 (4th July 2018) - Gubicza, Jenő; Németh, Regina; Park, Hyeji; Kim, Kyungbae; Kim, Jae‐Hun; Óvári, Mihály; Mohai, Miklós; Choe, Heeman
Abstract : Surface‐oxidized Co is a promising candidate as a negative electrode material in lithium ion batteries (LIBs). The stability of electrode materials in LIBs during charging/discharging is crucial from the viewpoint of their applications. In this study, experiments are carried out to investigate the influence of lithiation on the microstructure of Co foam processed by freeze casting. The main phase in the strut interiors of the as‐prepared foam was hcp‐Co with a grain size of ≈0.38 µm and a considerable lattice strain. Thirty cycles of charging/discharging caused no changes in the phase composition, the grain size, and microstrain in the struts. However, the crystalline surface oxide layer is practically amorphized and a strong oxygen/cobalt ratio gradient developed during lithiation; additionally, the foam is enriched with Li. These changes led to a fragmentation of the surface into scutes. Abstract : Experiments are carried out to investigate the influence of lithiation on the microstructure of Co foam processed by freeze casting. Thirty cycles of charging/discharging caused no changes in the phase composition, the grain size, and microstrain in the struts. However, the crystalline surface oxide layer is practically amorphized and a strong oxygen/cobalt ratio gradient developed during lithiation; additionally, the foam is enriched with Li. These changes led to a fragmentation of the surface into scutes.